Comparison of Anatomic and Functional Results after Retinotomy for Retinal Detachment in Pediatric and Adult Patients. Issue 3 (May 2013) - Stopa, Marcin; Kocięcki, Jarosław; Rakowicz, Piotr; Gotz-Więckowska, Anna; Rogulska, Monika
Purpose: We investigated characteristics and treatment outcomes of pediatric vs adult retinal detachment managed by retinotomy and retinectomy. Methods: This was a retrospective, nonrandomized, interventional study involving 20 pediatric patients and 25 adult patients operated with vitrectomy and retinectomy due to retinal detachment. Outcome measures included preoperative and postoperative visual acuity at 6 months and at final visit, postoperative proliferative vitreoretinopathy silicone oil removal, final intraocular pressure (IOP), and final anatomic success, defined as complete retinal reattachment. Results: Reattachment was observed in 60% (12/20) of pediatric patients and 88% (22/25) of adults at final visit (p=0.041). Statistically significant improvement in visual acuity was observed in adults (p<0.001) but not in children (p=0.360) due to large proportion of anatomic failure. Children required a higher number of further reoperations (p=0.008). Postoperative proliferative vitreoretinopathy was significantly more frequent in pediatric eyes (p=0.003). Conclusions: The clinical features and prognosis for pediatric retinotomies and retinectomies are different from those for adults. When a decision to perform retinotomy in children is made, we can anticipate significantly lower anatomic success than in adults. Even though the overall visual acuity was worse in children than in adults, 25% of pediatric eyes achieved 5/50 or better vision.